Isolation and identification of marine sulphate-reducing bacteria, desulfovibrio sp. and citrobacter freundii from Pasir Gudang, Malaysia - Sahrani, Fathul Karim; Ibrahim, Zaharah; Yahya, Adibah; Aziz, Madzlan (UKM, 2008)
In the attempt to isolate indigenous marine sulphate-reducing bacteria (SRB) from coastal samples, we obtained some swarm forming bacteria. The isolates were screening using Starkey's medium and detection of main groups of SRB were carried out using commercially kits (SRB BART kits, Droycon Bioconcepts Inc., Canada). From the growth characteristic, only two isolates were strongly suggested as marine SRB. Based on the 16S rRNA gene sequence analysis these SRB were closely related and could be designated as Desulfovibrio sp. and Citrobacter freundii, with the highest sequence similarity of 98% and 93%, respectively.